Sickness presenteeism and sickness absence over time: A UK employee perspective. Issue 1 (2nd January 2018) - Collins, Alison M.; Cartwright, Susan; Cowlishaw, Sean
ABSTRACT: This paper examined the influence of sickness presenteeism (SP), defined here as going to work despite illness, and sickness absenteeism (SA) behaviour on employee psychological well-being, work performance and perceived organisational commitment in a sample of 552 UK workers. Self-report measures were administered on 2 occasions, separated by 1 year, to employees from 4 public sector and 2 private sector organisations. Structural equation modelling was used to evaluate simultaneous influences of SP and SA on outcomes over time. Results suggested that employees reporting SP reported lower work performance in comparison to those reporting no SP, when measured concurrently but not over time. Employees reporting any SP in the previous 3 months showed relatively reduced psychological well-being but there was no significant association over time. Six or more days SP was associated with a reduction in employee perceptions that their organisation was committed to them, concurrently and over time. There were no significant influences of SA on any outcome measure. Our results strengthen previous research and suggest that SP, but not SA, has implications for individual outcomes. The findings have implications for the way organisations manage their sickness absence systems.